Queer Credibility in the Homonation-State: Interrogating the Affective Impacts of Credibility Assessments on Racialized Sexual Minority Refugee Claimants - Rinaldi, Jen; Fernando, Shanti (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2019)
This article critically appraises Canadian Immigration and Refugee Board decision-making that imposes burdens on diverse sexual orientation and gender identity and expression refugee claimants of colour to prove that they are queer according to homonationalist interpretations of queerness. This article examines decisions clustered around historical developments in the reception of racialized sexual minorities, including Canada (AG) v Ward, which made sexual minority refugee claims possible; Bill C-31, the immigration and refugee policy motivated by national security interests in the post-9/11 era; and 2017 guidelines designed to dispel misunderstandings about refugee claimants’ sexuality. Across this history, credibility assessments of refugee claims have undergone significant recalibrations, yet continue to reflect homonationalist values.